Motivation and leadership style influence the implementation of nursing care standards at Udayana University Hospital, Bali, Indonesia - Ni Putu Kusumayuni; I Ketut Suarjana; Cokorda Bagus Jaya Lesmana (Universitas Udayana, 2023)
Background and purpose: Leadership style, work environment and motivation of nurses are related to the implementation of nursing care standards. This study aims to determine factors associated with the implementation of nursing care standards in the hospital’s inpatient services. Methods: A cross-sectional study was conducted with all of the total 65 nurses working in the inpatient wards of the Udayana University Hospital, Bali in December 2022. Data were collected with a structured questionnaire covering nurses’ characteristics, leadership style, work environment, motivation and implementation of nursing care standards. Data were analyzed descriptively and analytically through path analysis assisted by a statistical software. Results: Of the 65 nurses, 69.2% were aged 26-30 years, 64.5% were female, 75.5% have worked under 3 years, and 75.4% have a bachelor's degree in nursing. There is a relationship between motivation (with a path coefficient of 0.603, p<0.001) and supportive leadership style (with a path coefficient of 0.615, p=0.028) with the implementation of standard nursing care. In addition, supportive leadership style (path coefficient 0.554, p=0.002), participative leadership style (path coefficient -0.353, p=0.061) and achievement-oriented leadership style (path coefficient 0.426, p=0.002) were associated with work motivation. Conclusion: Nurse motivation is directly associated, while supportive leadership style is indirectly related to the implementation of nursing care standards through increasing nurse motivation. Supportive, participatory leadership styles and achievement orientation are also directly related to nursing motivation. The hospital leaders and room manager must maintan and strengthen the participatory leadership style which will improve motivation and nursing care standard.